Waste Minimisation in Office Refurbishment Projects: An Australian Perspective - Hardie, M.; Miller, G.; Khan, Shahed (Bentham Science Publishers, 2011)
The refurbishment of commercial buildings is growing as a percentage of overall construction activity in Australia and this trend is likely to continue. Refurbishment generates a significant waste stream much of which is potentially reusable or recyclable. Despite this potential, several factors are known to unnecessarily inhibit the amount of recycling that actually occurs on renovation projects. In order to identify the reasons causing this reluctance, a process of project monitoring and expert consultation was carried out. Twenty three experts experienced in commercial refurbishment projects and three waste contractors with specific knowledge of construction waste were interviewed. Records of receipts for waste from a case study project reveal three principal factors inhibiting recycling rates: the presence of asbestos in the building; the continued occupation of the building during construction; and the breaking up of a large project into small separate contracts thereby reducing economies of scale. To ascertain the potential for improvement, current rates for reuse and recycling of materials were collected from the experts. The results revealed a considerable variation in practice between companies and indicated key areas which should be targeted to improve performance.